Oriented liquid crystal film and method for producing the same, optical film with adhesive and method for producing the same, and image display device
By using a combination of a photopolymerizable liquid crystal compound and a side chain liquid crystal polymer in an image display device, an oriented liquid crystal film with excellent hardness distribution is formed, and an adhesive layer is formed on its surface, thereby solving the agglomeration damage caused by the adhesive. and poor rework problems improve the durability and production efficiency of the image display device.
Patent Information
- Application Number
- CN201910777429.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-08-27
- Filing Date
- 2019-08-22
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2039-08-22
AI Technical Summary
Prior Art In an image display device, the use of adhesive can easily lead to the aggregation damage and poor rework of the oriented liquid crystal film, especially in high temperature and high humidity environments or drop impact test conditions, the optical film can easily peel off from the image display unit, and The need for large peeling forces during rework may lead to residual glue or interlayer peeling.
By adding a photopolymerizable liquid crystal compound and a side chain liquid crystal polymer to the liquid crystal layer oriented in a predetermined direction, the orientation and polymerization or crosslinking state of the liquid crystal molecules are adjusted to form an oriented liquid crystal film with excellent hardness distribution, and The surface forms an adhesive layer, controlling the thickness and distribution of the adhesive to reduce the agglomeration damage during rework.
The durability and reworkability of the image display device under high temperature and high humidity environment and harsh conditions are achieved, and the condensation damage and residual glue of the orientation liquid crystal film are reduced, and the production efficiency and yield of the image display device are improved.
Smart Images

Figure CN110865491B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an oriented liquid crystal film in which liquid crystal molecules are oriented, a method for producing the same, and an image display device having the oriented liquid crystal film. Furthermore, the present invention relates to an optical film with a pressure-sensitive adhesive having a pressure-sensitive adhesive layer on one surface of the oriented liquid crystal film, and a method for producing the same. Background Art
[0002] As an optical film with functions such as optical compensation of liquid crystal display devices and anti-external light reflection of organic EL elements, a liquid crystal film (oriented liquid crystal film) in which a liquid crystal compound is oriented in a specified direction is used. Since the birefringence of the oriented liquid crystal film is greater than that of a stretched polymer film, it is conducive to thinning or weight reduction.
[0003] When a thermotropic liquid crystal is used, a liquid crystal composition (solution) is applied to a substrate, heated so that the compound contained in the composition becomes a liquid crystal state, and then cooled to fix the orientation, thereby obtaining an oriented liquid crystal film. When the liquid crystal composition contains a photopolymerizable liquid crystal compound (liquid crystal monomer), after cooling, the liquid crystal monomer is polymerized or cross-linked by light irradiation to improve stability.
[0004] Liquid crystal compounds can orient liquid crystal molecules in a predetermined direction by shear force when applied to a substrate or by the orientation restriction force of an orientation film, and can obtain an oriented liquid crystal film with various optical anisotropies. For example, in a vertically oriented liquid crystal film in which liquid crystal molecules with positive refractive index anisotropy are oriented in the normal direction (thickness direction) of the film surface, the refractive index (anomalous refractive index) nz in the orientation direction of the liquid crystal molecules, i.e., the thickness direction, is greater than the refractive index (normal refractive index) nx and ny in the plane, and can be used as a positive C plate with a refractive index anisotropy of nz>nx=ny.
[0005] Since there are very few substances that spontaneously perform vertical alignment, a substrate with a vertical alignment film is generally used in the production of a vertical alignment liquid crystal film. Patent Document 1 discloses that a vertical alignment liquid crystal film can be formed on a substrate without a vertical alignment film by using a composition comprising a side chain type liquid crystal polymer having a monomer unit having a liquid crystal segment side chain and a monomer unit having a non-liquid crystal segment side chain, and a photopolymerizable liquid crystal monomer. Patent Document 1 records the idea that the non-liquid crystal segment side chain of the liquid crystal polymer has the function of promoting vertical alignment.
[0006] An image display device can be obtained by laminating an oriented liquid crystal film together with an optical film such as a polarizing plate to the surface of an image display unit. For laminating the oriented liquid crystal film on the image display unit, an adhesive is generally used. When laminating the optical film on the image display unit via an adhesive, defects such as mixing of bubbles or deviation of the attachment position may sometimes occur. In addition, after laminating the optical film on the image display unit, defects caused by defects of the optical film may sometimes be detected. In the case of such a defect, the optical film may be peeled off from the image display unit (rework).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 4174192 Summary of the invention
[0010] Problems to be solved by the invention
[0011] Image display devices are required to have higher durability, and the optical film is required not to peel off from the image display unit even when exposed to high temperature and high humidity for a long time or under harsh conditions such as drop impact tests. By using an adhesive with high adhesion in the bonding of the image display unit and the optical film, it is possible to suppress the peeling of the optical film from the image display unit in the use environment of the image display device.
[0012] On the other hand, if an adhesive with high adhesive strength is used, a large peeling force is required during rework, which may cause adhesive residue on the surface of the image display unit (residual adhesive) or delamination between layers of the optical film (interlayer delamination) and other undesirable conditions (rework failure). In particular, the inventors' research has revealed that when the optical film includes an oriented liquid crystal film, the large peeling force during rework may easily cause cohesive failure of the oriented liquid crystal film, and this may easily cause rework failure due to residual adhesive or interlayer delamination.
[0013] In view of the above circumstances, an object of the present invention is to provide an oriented liquid crystal film in which occurrence of rework failure is suppressed when the film is bonded to an image display unit via an adhesive.
[0014] Means for solving problems
[0015] In view of the above situation, the inventors conducted research and found that when the ratio of horizontal loads at a specified depth from the surface is within a specified range, cohesion failure of the oriented liquid crystal film is unlikely to occur, and rework defects caused by bonding with the image display unit via an adhesive can be suppressed, thereby completing the present invention.
[0016] The present invention relates to an oriented liquid crystal film made of a liquid crystal layer in which liquid crystal molecules are oriented in a predetermined direction and a method for producing the same. The oriented liquid crystal film contains two or more compounds, at least one of which is a polymer of a photopolymerizable liquid crystal compound.
[0017] As examples of other compounds included in the oriented liquid crystal film, polymers can be cited. As examples of polymers, side chain liquid crystal polymers can be cited. For example, the oriented liquid crystal film can promote the vertical orientation of the photopolymerizable liquid crystal compound by including a side chain liquid crystal polymer having a monomer unit containing a liquid crystal segment side chain and a monomer unit containing a non-liquid crystal segment side chain in addition to the polymer containing the photopolymerizable liquid crystal compound, thereby obtaining a vertically oriented liquid crystal film.
[0018] The oriented liquid crystal film of the polymer containing the photopolymerizable liquid crystal compound is obtained, for example, by coating a liquid crystal composition containing the photopolymerizable liquid crystal compound and a non-photopolymerizable compound (such as the above-mentioned side chain liquid crystal polymer) on a film substrate, heating the liquid crystal composition to orient the liquid crystal molecules in a specified direction, and polymerizing or cross-linking the photopolymerizable liquid crystal compound by light irradiation. As a film substrate, a film without an oriented film can also be used. The film substrate without an oriented film can also be a stretched film with an in-plane retardation of 10 to 500 nm.
[0019] The oriented liquid crystal film preferably has a maximum horizontal load F at a depth of 30 nm from the surface. 30 is the maximum horizontal load F at a depth of 15 nm from the surface 15 For example, by adjusting the light irradiation amount when the photopolymerizable liquid crystal compound is polymerized or cross-linked, the F of the oriented liquid crystal film can be adjusted. 30 / F 15 The cumulative irradiation light amount when polymerizing or cross-linking the photopolymerizable liquid crystal compound is preferably 100 to 370 mJ / cm 2 .
[0020] Examples of the use of the oriented liquid crystal film include an optical film with an adhesive layer on one main surface of the oriented liquid crystal film. The optical film with an adhesive may include another film bonded to the other main surface of the oriented liquid crystal film via an adhesive layer.
[0021] An optical film with an adhesive having an adhesive layer on one surface of an oriented liquid crystal film and another film bonded via the adhesive layer on the other surface is obtained by, for example, forming an oriented liquid crystal film on a film substrate, bonding the other film to the oriented liquid crystal film via the adhesive layer, peeling off the film substrate, and laminating the adhesive layer on the oriented liquid crystal film. The adhesive bonding the oriented liquid crystal film to the other film may also be a photocurable adhesive.
[0022] Effects of the Invention
[0023] After the oriented liquid crystal film of the present invention is bonded to the image display unit via an adhesive, cohesive failure is unlikely to occur during rework, and the reworkability is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a cross-sectional view showing one embodiment of an optical film with a pressure-sensitive adhesive.
[0025] Figure 2 This is a conceptual diagram showing an example of a process for producing an optical film with a pressure-sensitive adhesive.
[0026] Figure 3 It is a cross-sectional view showing an example of a stacked structure of an image display device.
[0027] Figure 4 This is a graph showing the relationship between the integrated light intensity and the horizontal load when the aligned liquid crystal film of the example is produced.
[0028] Figure 5 This is a TEM cross-sectional observation image of the aligned liquid crystal film of the example.
[0029] Explanation of symbols
[0030] 1 Oriented liquid crystal film
[0031] 11 substrate surface
[0032] 12 Air surface
[0033] 2 Adhesive layer
[0034] 3 Adhesive layer
[0035] 4 Membrane
[0036] 8 membrane substrate
[0037] 9 Diaphragm
[0038] 50 Image display unit DETAILED DESCRIPTION
[0039] The oriented liquid crystal film of the present invention is made of a liquid crystal layer in which liquid crystal molecules are oriented in a predetermined direction. The liquid crystal layer contains two or more compounds, at least one of which is a polymer of a photopolymerizable liquid crystal compound.
[0040] In the oriented liquid crystal film of the present invention, the horizontal load F at a depth of 30 nm from the surface is 30 is the horizontal load F at a depth of 15 nm from the surface 151 to 2.2 times of the depth. The horizontal load is the load when the nanoindenter is pressed into the specified depth, the indenter is moved in the horizontal direction (direction perpendicular to the depth direction), and the sample is relatively moved. The horizontal load is an indicator of the hardness of the sample at a specified depth. Different horizontal loads depending on the depth of indentation mean that the sample has a hardness distribution in the depth direction.
[0041] The F of the oriented liquid crystal film of the present invention 30 / F 15 The hardness distribution in the depth direction near the surface is small when the hardness is less than 2.2. Therefore, after the oriented liquid crystal film is attached to the image display unit using an adhesive, it is not easy to cause cohesion failure of the oriented liquid crystal film during rework, and the undesirable conditions such as residual adhesive on the image display unit (rework defect) can be suppressed.
[0042] Figure 1 This is a cross-sectional view showing one embodiment of an optical film with a pressure-sensitive adhesive in which a pressure-sensitive adhesive layer 2 is attached to an oriented liquid crystal film 1 . Figure 1 The optical film with pressure-sensitive adhesive comprises a pressure-sensitive adhesive layer 2 on one main surface of an oriented liquid crystal film 1 and a film 4 bonded to the other surface via a pressure-sensitive adhesive layer 3. A separator 9 is temporarily bonded to the surface of the pressure-sensitive adhesive layer 2.
[0043] Figure 2 A to 2D show an example of a manufacturing process of an optical film with an adhesive. First, a liquid crystal composition containing a liquid crystal compound is applied to a film substrate 8, and photopolymerization is performed in a state where the liquid crystal molecules are oriented in a predetermined direction to fix the orientation state of the liquid crystal molecules, thereby obtaining a laminate 10 ( Figure 2 A) In the laminate 10, the surface of the oriented liquid crystal film 1 in contact with the film substrate 8 is defined as the "substrate surface", and the surface on the opposite side is defined as the "air surface".
[0044] The film 4 is bonded to the air surface 12 of the oriented liquid crystal film 1 via the adhesive layer 3. Figure 2 B), the film substrate 8 is peeled off from the substrate surface 11 of the oriented liquid crystal film 1 ( Figure 2 C). By laminating the adhesive layer 2 on the substrate surface 11 of the oriented liquid crystal film 1 ( Figure 2 D) to obtain an optical film with a pressure-sensitive adhesive in which the pressure-sensitive adhesive layer 2 is provided on the substrate surface 11 of the oriented liquid crystal film 1.
[0045] The optical film with a pressure-sensitive adhesive is used, for example, for forming an image display device. Figure 3 The cross-sectional view shows a laminated structure example of an image display device having an optical film with a pressure-sensitive adhesive, and an oriented liquid crystal film 1 is bonded to the surface of an image display unit 50 via a pressure-sensitive adhesive layer 2. The image display unit 50 may be a liquid crystal unit or an organic EL unit.
[0046] [Oriented liquid crystal film]
[0047] The oriented liquid crystal film is made of a liquid crystal layer in which the liquid crystal molecules are oriented in a predetermined direction and the orientation state is fixed. Since the oriented liquid crystal film has a significantly larger birefringence than a film made of a non-liquid crystal material, the thickness of the optically anisotropic element having the desired retardation can be significantly reduced. The thickness of the oriented liquid crystal film is about 0.5 to 7 μm, preferably 1 to 5 μm.
[0048] The liquid crystal layer contains two or more compounds, at least one of which is a polymer of a photopolymerizable liquid crystal compound. The oriented liquid crystal film is obtained by coating a liquid crystal composition on a film substrate, heating the liquid crystal composition to align the liquid crystal molecules in a predetermined direction, and polymerizing or cross-linking the liquid crystal compound by light irradiation.
[0049] <Liquid Crystal Composition>
[0050] The liquid crystal composition comprises two or more compounds. The liquid crystal composition comprises at least one photopolymerizable liquid crystal compound. The liquid crystal compound contained in the liquid crystal composition preferably has a nematic phase (nematic liquid crystal). The liquid crystal compound may have a lyotropic or thermotropic mechanism of expression of liquid crystal properties. In order to obtain a vertically aligned liquid crystal film, it is preferred to use a thermotropic liquid crystal.
[0051] (Photopolymerizable liquid crystal compound)
[0052] The photopolymerizable liquid crystal compound (monomer) has a mesogenic group and at least one photopolymerizable functional group in one molecule. The temperature at which the liquid crystal monomer exhibits liquid crystallinity (liquid crystal phase transition temperature) is preferably 40 to 100°C, more preferably 50 to 90°C, and further preferably 55 to 85°C.
[0053] In the preparation of oriented liquid crystal film, the liquid crystal composition is coated on the substrate, heated to above the liquid crystal phase transition temperature to align the liquid crystal molecules, cooled to below the glass transition temperature to fix the orientation, and irradiated with light to perform photocuring (polymerization and / or crosslinking) of the liquid crystal monomer. Through light irradiation, the photopolymerizable functional groups of the liquid crystal monomer react to obtain a polymer of the photopolymerizable liquid crystal compound. The polymer after photocuring is non-liquid crystal and will not produce a transition between the liquid crystal phase, the glass phase, and the crystalline phase due to temperature changes. Therefore, if photocuring is performed in a state where the liquid crystal monomer is oriented in a specified direction, an oriented liquid crystal film that is not easily affected by temperature changes and has excellent stability is obtained.
[0054] As the mesogenic group of the liquid crystal monomer, there can be listed cyclic structures such as biphenyl, phenylbenzoate, phenylcyclohexyl, azoxyphenyl, azomethine, azophenyl, phenylpyrimidinyl, diphenylethynyl, diphenylbenzoate, bicyclohexyl, cyclohexylphenyl, and terphenyl. The ends of these cyclic units may also have substituents such as cyano, alkyl, alkoxy, and halogen groups.
[0055] As the photopolymerizable functional group, (meth)acryloyl, epoxy, vinyl ether, etc. can be cited. Among them, (meth)acryloyl is preferred. The photopolymerizable liquid crystal monomer is preferably a monomer having two or more photopolymerizable functional groups in one molecule. Since a cross-linked structure is introduced into the liquid crystal layer after photopolymerization by using a liquid crystal monomer containing two or more photopolymerizable functional groups, there is a tendency for the durability of the oriented liquid crystal film to be improved.
[0056] As liquid crystal monomer, any appropriate liquid crystal monomer can be adopted. For example, the polymerizable mesogen compounds recorded in International Publication No. 00 / 37585, U.S. Patent No. 5211877, U.S. Patent No. 4388453, International Publication No. 93 / 22397, European Patent No. 0261712, German Patent No. 19504224, German Patent No. 4408171, British Patent No. 2280445, etc. can be used. As a specific example of liquid crystal monomer, for example, BASF company "Paliocolor LC242", Merck company "E7", Wacker-Chem company "LC-Sillicon-CC3767" etc. can be listed.
[0057] Examples of the photopolymerizable liquid crystal monomer having a mesogenic group and a plurality of (meth)acryloyl groups in one molecule include compounds represented by the following general formula (IV).
[0058]
[0059] In formula (IV), R is a hydrogen atom or a methyl group, A and D are each independently 1,4-phenylene or 1,4-cyclohexylene, B is 1,4-phenylene, 1,4-cyclohexylene, 4,4'-biphenylene or 4,4'-bicyclohexylene, Y and Z are each independently -COO-, -OCO- or -O-. g and h are each independently an integer of 2 to 6.
[0060] (Liquid Crystal Polymer)
[0061] In the liquid crystal composition, it is preferred that in addition to the liquid crystal monomer, a compound for controlling the orientation of the liquid crystal monomer in a predetermined direction is also included. By including the compound for controlling the orientation of the liquid crystal monomer in the liquid crystal composition, a liquid crystal layer in which the liquid crystal molecules are oriented in a predetermined direction can be formed even when a substrate without an orientation film is used.
[0062] The compound for controlling the alignment of the liquid crystal monomer may be a polymer or a low molecular weight compound. For example, in order to vertically align the liquid crystal monomer, it is preferable to include a side chain type liquid crystal polymer in the liquid crystal composition.
[0063] The side chain type liquid crystal polymer may be a homopolymer or a copolymer. The side chain type liquid crystal polymer may only contain monomer units having liquid crystal segment side chains, or may contain monomer units having no liquid crystal segment on the side chains in addition to monomer units having liquid crystal segment side chains. As monomer units having no liquid crystal segment on the side chains, monomer units having no side chains and monomer units having non-liquid crystal segments on the side chains may be listed.
[0064] The polymer has a liquid crystal segment on the side chain, thereby showing liquid crystal properties, and when the liquid crystal composition is heated to a specified temperature, there is a tendency for the polymer to be oriented in a specified direction. In addition, the polymer has a non-liquid crystal segment on the side chain, so that the photopolymerizable liquid crystal monomer contained in the liquid crystal composition and the polymer are vertically oriented together. By aligning the liquid crystal monomer with the orientation of the side chain liquid crystal polymer and fixing the orientation state, a vertically oriented liquid crystal film can be obtained.
[0065] As the monomer having a liquid crystal segment side chain, a polymerizable compound having a nematic liquid crystal substituent containing a mesogenic group can be cited. As the mesogenic group, the groups exemplified above as the mesogenic groups of the liquid crystal monomer can be cited. Among them, as the mesogenic group, a mesogenic group having a biphenyl group or a phenylbenzoate group is preferred.
[0066] Examples of monomers having a non-liquid crystal segment side chain include polymerizable compounds having a linear substituent such as a long chain alkyl group having at least 7 carbon atoms. Examples of polymerizable functional groups of liquid crystal monomers and non-liquid crystal monomers include (meth)acryloyl groups.
[0067] As the side chain type liquid crystal polymer, a copolymer having a liquid crystal monomer unit represented by the general formula (I) and a non-liquid crystal monomer unit represented by the general formula (II) is preferably used.
[0068]
[0069] In formula (I), R 1is a hydrogen atom or a methyl group, R 2 is a cyano group, a fluoro group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and X 1 For -CO 2 - or -OCO-. a is an integer of 1 to 6, and b and c are 1 or 2, respectively, independently.
[0070] In formula (II), R 3 is a hydrogen atom or a methyl group, R 4 It is an alkyl group having 7 to 22 carbon atoms, a fluoroalkyl group having 1 to 22 carbon atoms, or a group represented by the following general formula (III).
[0071]
[0072] In formula (III), R 5 is an alkyl group having 1 to 5 carbon atoms, and d is an integer of 1 to 6.
[0073] The ratio of the liquid crystal monomer unit to the non-liquid crystal monomer unit in the side chain liquid crystal polymer is not particularly limited. When the ratio of the non-liquid crystal monomer unit is small, the orientation of the photopolymerizable liquid crystal compound accompanying the orientation of the side chain liquid crystal polymer sometimes becomes insufficient, and the orientation of the liquid crystal layer after photocuring becomes uneven. On the other hand, when the ratio of the liquid crystal monomer unit is small, the side chain liquid crystal polymer becomes difficult to show liquid crystal monodomain orientation. Therefore, the ratio of the non-liquid crystal monomer to the total of the liquid crystal monomer unit and the non-liquid crystal monomer unit is preferably 0.01 to 0.8 in terms of molar ratio, more preferably 0.1 to 0.6, and further preferably 0.15 to 0.5. From the viewpoint of both the film-forming property and the orientation property of the liquid crystal composition, the weight average molecular weight of the side chain liquid crystal polymer is preferably about 2000 to 100000, and more preferably about 2500 to 50000.
[0074] Side chain liquid crystal polymers can be polymerized by various known methods. For example, when the monomer unit has a (meth)acryloyl group as a polymerizable functional group, a side chain liquid crystal polymer having a liquid crystal segment and a non-liquid crystal segment can be obtained by free radical polymerization using light or heat.
[0075] (composition)
[0076] The ratio of the photopolymerizable liquid crystal compound (monomer) to other compounds in the liquid crystal composition is not particularly limited. From the viewpoint of obtaining an oriented liquid crystal film with high durability, the content of the photopolymerizable liquid crystal compound is preferably greater than the content of other compounds. With respect to a liquid crystal composition comprising a photopolymerizable liquid crystal compound and a liquid crystal polymer, from the viewpoint of obtaining a highly oriented liquid crystal film with high durability and orientation uniformity, the content (weight) of the photopolymerizable liquid crystal compound is preferably 1.5 to 15 times the content of the liquid crystal polymer, more preferably 2 to 10 times, and further preferably 2.5 to 6 times.
[0077] In order to promote the curing of the photopolymerizable liquid crystal compound by light irradiation, the liquid crystal composition preferably contains a photopolymerization initiator. As the photopolymerization initiator, a substance (photoradical generator) that generates free radicals by light irradiation is preferred. The content of the photopolymerization initiator in the liquid crystal composition is generally about 0.5 to 20 parts by weight, preferably about 3 to 15 parts by weight, and more preferably about 5 to 10 parts by weight relative to 100 parts by weight of the photopolymerizable liquid crystal compound.
[0078] Liquid crystal compositions can be prepared by mixing a photopolymerizable liquid crystal compound with other compounds (e.g., side chain liquid crystal polymers) and a photopolymerization initiator with a solvent. The solvent is not particularly limited as long as it can dissolve the photopolymerizable liquid crystal compound and does not corrode the film substrate (or has low corrosiveness). Examples include halogenated hydrocarbons such as chloroform, dichloromethane, carbon tetrachloride, dichloroethane, tetrachloroethane, trichloroethylene, tetrachloroethylene, chlorobenzene, and o-dichlorobenzene; phenols such as phenol and p-chlorophenol; aromatic hydrocarbons such as benzene, toluene, xylene, methoxybenzene, and 1,2-dimethoxybenzene; acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, cyclopentanone, 2-hydroxy-1-nitropropene; -pyrrolidone, N-methyl-2-pyrrolidone and other ketone solvents; ethyl acetate, butyl acetate and other ester solvents; tert-butyl alcohol, glycerol, ethylene glycol, triethylene glycol, ethylene glycol monomethyl ether, diethylene glycol dimethyl ether, propylene glycol, dipropylene glycol, 2-methyl-2,4-pentanediol and other alcohol solvents; dimethylformamide, dimethylacetamide and other amide solvents; acetonitrile, butyronitrile and other nitrile solvents; diethyl ether, dibutyl ether, tetrahydrofuran and other ether solvents; ethyl cellosolve, butyl cellosolve, etc. The concentration of the liquid crystal composition is usually about 3 to 50% by weight, preferably about 7 to 35% by weight.
[0079] <Membrane substrate>
[0080] As the substrate for coating the liquid crystal composition, a film substrate is preferably used. By using a film substrate, a series of steps from coating the liquid crystal composition on the substrate to curing the liquid crystal monomer by photopolymerization can be performed in a roll-to-roll manner, thereby improving the productivity of the oriented liquid crystal film.
[0081] The film substrate has a first main surface and a second main surface, and a liquid crystal composition is coated on the first main surface. The resin material constituting the film substrate is not particularly limited as long as it is insoluble in the solvent of the liquid crystal composition and has heat resistance when heated for orienting the liquid crystal composition. Polyesters such as polyethylene terephthalate and polyethylene naphthalate can be listed; polyolefins such as polyethylene and polypropylene; cyclic polyolefins such as norbornene polymers; cellulose polymers such as diacetyl cellulose and triacetyl cellulose; acrylic polymers; styrene polymers; polycarbonate, polyamide, polyimide, etc. Among them, from the perspective of excellent fluidity during molding and easy to obtain a film with high smoothness, it is particularly preferred to use a norbornene polymer film as a film substrate. From the perspective of excellent peelability when transferring the oriented liquid crystal film to other films, etc., a norbornene polymer film is also preferred. As a norbornene polymer, Zeonor, Zeonex, and Arton made by JSR made by Zeon Corporation of Japan can be listed.
[0082] An alignment film may also be provided on the film substrate. The alignment film may be selected appropriately according to the type of liquid crystal compound or the material of the substrate. As an alignment agent for forming the alignment film, lecithin, stearic acid, hexadecyltrimethylammonium bromide, octadecylamine hydrochloride, monocarboxylic acid chromium complex, silane coupling agent or organosilanes such as siloxane compounds, perfluorodimethylcyclohexane, tetrafluoroethylene, polytetrafluoroethylene, etc. may be cited.
[0083] As described above, when the liquid crystal composition contains a compound that promotes the alignment of the liquid crystal in a predetermined direction in addition to the photopolymerizable liquid crystal compound, a vertically aligned liquid crystal film can be formed even when a substrate without an alignment film is used. By making the alignment film unnecessary, the versatility of the film substrate is improved, and the process can be simplified and the manufacturing cost can be reduced.
[0084] As the film substrate, a stretched film may also be used. By stretching the film, the unevenness such as the die line during film formation is smoothed, so there is a tendency that the smoothness of the film substrate is improved and the arithmetic mean roughness Ra becomes smaller. From the aspect of high surface uniformity, it is particularly preferred to use a biaxially stretched film as the film substrate.
[0085] In-plane retardation R of stretched film used as film substrate 0Usually more than 10nm. In the case where the film substrate is a stretched film with an in-plane retardation of more than 10nm, the polymer constituting the film is preferentially oriented along a specified direction (slow axis direction or fast axis direction). Since the orientation of the polymer of the film substrate has an orientation restriction force that causes the liquid crystal molecules to be horizontally oriented, in the absence of a vertically oriented film, the vertical orientation of the liquid crystal molecules is sometimes hindered and orientation defects occur. As described in detail below, by reducing the heating temperature when the liquid crystal molecules are vertically oriented, a vertically oriented liquid crystal film with fewer orientation defects can be obtained even when a stretched film substrate is used.
[0086] If the in-plane retardation of the film substrate is too large, the temperature range in which alignment defects can be reduced may be narrowed, and the liquid crystal phase transition may become difficult in this temperature range. 0 It is preferably 500 nm or less, more preferably 300 nm or less, and further preferably 200 nm or less.
[0087] The thickness of the film substrate is not particularly limited, but is generally about 10 to 200 μm in consideration of handling properties, etc. The in-plane birefringence Δn (in-plane retardation R 0 The value obtained by dividing by the thickness) is preferably 0.01 or less, more preferably 0.008 or less, and further preferably 0.006 or less.
[0088] The arithmetic mean roughness Ra of the first main surface of the film substrate is preferably less than 3nm, more preferably less than 2nm, and further preferably less than 1.5nm. By applying the liquid crystal composition on the film substrate surface with small Ra and high smoothness, there is a tendency that the orientation defects of the oriented liquid crystal film are reduced. As mentioned above, by stretching the film, there is a tendency that the Ra of the film becomes smaller. Therefore, by using a stretched film substrate, there is a tendency that the orientation defects of the oriented liquid crystal film are reduced.
[0089] Since the surface shape of the first main surface of the film substrate is transferred to the oriented liquid crystal film formed thereon, the Ra of the substrate surface of the oriented liquid crystal film becomes approximately equal to the Ra of the first main surface of the substrate. Therefore, in the case of using a film substrate with a Ra of less than 3nm on the first main surface, the Ra of the substrate surface of the oriented liquid crystal film also becomes less than 3nm in most cases. In addition, there is a tendency that the Ra of the air surface during the coating of the liquid crystal composition becomes less than the Ra of the substrate surface. Therefore, if a film substrate with a Ra of less than 3nm on the first main surface is used, the arithmetic mean roughness of the two sides of the oriented liquid crystal film becomes less than 3nm in most cases.
[0090] In order to set the arithmetic mean roughness to the above range, the film substrate is preferably a film that does not contain fillers inside. The film with high smoothness on the surface without fillers is low in slip, so sometimes adhesion or poor handling or winding in the roll-to-roll process is produced. In order to prevent adhesion or poor handling caused by high smoothness, the method of laminating other films with high slip on the film substrate or the method of setting an easy-slip layer on the film substrate can be listed. In the case of laminating other films on the film substrate, from the viewpoint of suppressing the bad conditions (bad orientation of liquid crystal or optical defects, etc.) caused by the transfer of the adhesive layer, etc. to the first main surface (the surface of the liquid crystal composition), it is preferably laminated to the second main surface (the surface on the opposite side of the coating surface of the liquid crystal composition). Wherein, in the roll-to-roll process, when the film substrate is wound, the adhesive attached to the second main surface, etc. is transferred to the first main surface, which may become the cause of poor orientation or optical defects.
[0091] Therefore, it is preferred to provide a slippery layer on at least one surface of the film substrate to improve the slipperiness. Examples of the slippery layer include a layer containing a fine filler having an average particle size of 100 nm or less in a binder such as polyester or polyurethane.
[0092] When the oriented liquid crystal film 1 and the film 4 are bonded together and then peeled off from the film substrate 8 (see Figure 2 B and Figure 2 C) and from the viewpoint of preventing undesirable situations such as transfer of the easy slip layer to the oriented liquid crystal film 1 when peeling from the film substrate 8, the film substrate 8 preferably does not have an easy slip layer on the surface on which the liquid crystal composition is applied. That is, it is preferred to use a film substrate having an easy slip layer on the second main surface and not having an easy slip layer on the first main surface.
[0093] <Formation of Aligned Liquid Crystal Film on Film Substrate>
[0094] The liquid crystal composition is applied on a film substrate, and the liquid crystal compound is heated to be aligned in a liquid crystal state, and then cooled to fix the alignment. The photopolymerizable liquid crystal compound is polymerized or cross-linked by light irradiation to obtain an aligned liquid crystal film.
[0095] The method for coating the liquid crystal composition on the film substrate is not particularly limited, and can be spin coating, die coating, contact roll coating, gravure coating, reverse coating, spray coating, Meyer rod coating, roll knife coating, air knife coating, etc. After the solution is applied, the solvent is removed to form a liquid crystal composition layer on the film substrate. The coating thickness is preferably adjusted in such a way that the thickness of the liquid crystal composition layer after the solvent is dried (the thickness of the oriented liquid crystal film) is about 0.5 to 7 μm.
[0096] The liquid crystal phase is formed by heating the liquid crystal composition layer formed on the film substrate, and the liquid crystal compound is oriented. The heating temperature is not particularly limited, and is usually about 40 to 200°C. If the heating temperature is too low, there is a tendency that the transition to the liquid crystal phase becomes insufficient, and if the heating temperature is too high, there is a tendency that the orientation defects increase. Therefore, the heating temperature is preferably 45 to 100°C, more preferably 50 to 95°C, and further preferably 55 to 90°C. The heating time can be adjusted in a manner that the transition to the liquid crystal phase becomes sufficient, and is usually about 30 seconds to 30 minutes.
[0097] When a stretched film substrate without an oriented film is used, there is a tendency that the horizontal orientation restriction force caused by the molecular orientation of the film substrate becomes stronger as the heating temperature rises. When a liquid crystal composition is applied to a stretched film substrate without an oriented film and used to make a vertically oriented liquid crystal film, it is preferably heated at a low temperature within the temperature range where the liquid crystal polymer transforms into a liquid crystal phase. The heating temperature T (°C) during orientation is preferably 100-3.5×10 3 Δn is less than Δn. Δn is the in-plane birefringence of the stretched film substrate. The heating temperature T is more preferably 100-4×10 3 Δn is less than 100-4.5×10 3 In addition, the heating temperature T is preferably 100-0.1R 0 Below, more preferably 100-0.12R 0 Below, more preferably 100-0.13R 0 Below. 0 is the in-plane retardation of the stretched film substrate.
[0098] As described above, by using a stretched film substrate with high smoothness and adjusting the heating temperature T when orienting the liquid crystal, even when using a substrate without an orientation film, it is possible to suppress the orientation failure of the vertically oriented liquid crystal film. The light leakage (orientation failure) of the vertically oriented liquid crystal film observed under a polarizing microscope is preferably 0.1% per 1 cm 2 The number of defective orientation is 1 or less, more preferably 0.7 or less, and further preferably 0.5 or less. The number of defective orientation is determined as an average value observed at 10 locations in the film surface.
[0099] After heating, the orientation is fixed by cooling to a temperature below the glass transition temperature. The cooling method is not particularly limited, for example, it can be taken out of the heated atmosphere and cooled to room temperature. Forced cooling such as air cooling and water cooling can also be performed.
[0100] By irradiating the liquid crystal composition layer after the orientation is fixed, the photopolymerizable liquid crystal compound is polymerized or cross-linked, so that the orientation of the photopolymerizable liquid crystal compound is fixed, and the durability of the oriented liquid crystal film is improved. As the irradiated light, it is sufficient to select light of a wavelength to which the photopolymerization initiator has sensitivity, and ultraviolet rays are generally used. As the irradiation light source of ultraviolet rays, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, LEDs, black light lamps, chemical lamps, etc. are used. In order to promote the photopolymerization reaction, the light irradiation is preferably carried out under an inert gas atmosphere such as nitrogen.
[0101] In the case where the photopolymerizable liquid crystal compound contains a non-photopolymerizable compound (e.g., a polymer) in addition to the photopolymerizable liquid crystal compound, the photopolymerizable compound is cured by light irradiation, whereas the non-photopolymerizable compound does not react. If the non-photopolymerizable compound is unevenly present in the coating layer of the liquid crystal composition, the hardness of the oriented liquid crystal film will have local differences as the photocuring reaction proceeds.
[0102] For example, if a liquid crystal composition containing a photopolymerizable liquid crystal compound and a side chain liquid crystal polymer is coated on a film substrate 8, there is a tendency for the side chain liquid crystal polymer to be unevenly present near the interface with the film substrate 8 and near the air interface in the coating layer. If photocuring is performed in a state where the polymer is unevenly present near the interface, the hardness of the central part in the thickness direction of the liquid crystal layer (the region with a high concentration of the photopolymerizable compound) increases as the photocuring proceeds, while the hardness near the interface (the region with a low concentration of the photopolymerizable compound and a high concentration of the polymer) changes little, so the hardness difference in the thickness direction (depth direction) increases. Along with this, the horizontal load F at a depth of 15 nm from the surface (interface) is 15 The horizontal load F at a depth of 30 nm 30 Ratio F 30 / F 15 There is a tendency to grow larger.
[0103] In order to 30 / F 15 When F is set to 2.2 or less, it is preferred to adjust the light irradiation amount during photocuring to suppress excessive progress of photocuring. The larger the light irradiation amount during photocuring, the more the photocuring of the photopolymerizable liquid crystal compound proceeds. 30 / F 15 The tendency to grow larger.
[0104] The cumulative irradiation light intensity during photocuring is preferably 370 mJ / cm 2 Below, more preferably 350mJ / cm 2On the other hand, if the light irradiation amount is too small, the curing of the photopolymerizable compound becomes insufficient, and the hardness or heating durability of the oriented liquid crystal film tends to decrease. Therefore, the cumulative irradiation light amount during photocuring is preferably 100 mJ / cm 2 More preferably, 130 mJ / cm 2 More preferably, 150 mJ / cm 2 The cumulative irradiation light quantity during the photocuring of the aligned liquid crystal film is the cumulative light quantity of UVA (wavelength 320 to 390 nm) measured using a cumulative light quantity meter.
[0105] As mentioned above, the F of the oriented liquid crystal film 30 / F 15 Preferably, it is 1 to 2.2. 30 / F 15 It is more preferably 1.1 to 2.1, and even more preferably 1.2 to 2. 30 / F 15 If the above range is used, after the oriented liquid crystal film is attached to the image display unit using an adhesive, cohesive failure of the oriented liquid crystal film is less likely to occur during rework, and rework defects can be suppressed. 30 / F 15 It may be 1.3 or more, 1.4 or more, or 1.5 or more. 30 / F 15 It may be 1.9 or less or 1.8 or less.
[0106] From the viewpoint of making the aligned liquid crystal film have sufficient hardness, the horizontal load F at a depth of 15 nm from the surface is 15 It is preferably 1 μN or more, more preferably 2 μN or more, and even more preferably 2.5 μN or more. 15 It may also be 3 μN or more or 3.5 μN or more. 30 / F 15 Keeping in mind the appropriate range, F 15 It is preferably 20 μN or less, more preferably 15 μN or less, and even more preferably 10 μN or less. 15 It may be 8 μN or less, 6 μN or less, 5 μN or less, or 4.5 μN or less.
[0107] If the light irradiation during photocuring is large and the curing of the photopolymerizable compound progresses, there is a tendency for the horizontal load of the oriented liquid crystal film to increase. On the other hand, if the polymer is unevenly present near the interface, even if the curing of the photopolymerizable compound progresses, the change in the horizontal load near the interface is small. 15For example, the properties of the polymer contained in the liquid crystal composition have a great influence. Therefore, by selecting the structure or molecular weight of the polymer contained in the liquid crystal composition, the F 15 Set to the above range.
[0108] Horizontal load F at a depth of 30 nm from the surface of the oriented liquid crystal film 30 It is preferably 1.5 μN or more, more preferably 2.5 μN or more, and even more preferably 3 μN or more. 30 It may also be 3.5 μN or more, 4 μN or more, 4.5 μN or more, or 5 μN or more. 30 / F 15 Keeping in mind the appropriate range, F 30 It is preferably 40 μN or less, more preferably 25 μN or less, and even more preferably 15 μN or less. 30 It may be 10 μN or less, 9 μN or less, or 8 μN or less.
[0109] Even when the polymer is unevenly present near the interface, the concentration of the photopolymerizable compound is high and the concentration of the polymer is low at a depth of about 30 nm from the surface, so there is a tendency for the photopolymerizable compound to be cured as the curing of the photopolymerizable compound proceeds. 30 Therefore, by adjusting the light irradiation amount during photocuring, F 30 Adjust to the desired range.
[0110] [Application of oriented liquid crystal film]
[0111] The oriented liquid crystal film can be used as an optical film for display for the purpose of viewing angle compensation, etc. The oriented liquid crystal film can be used in a state of being laminated with a film substrate, or can be used after being peeled off from the film substrate. The oriented liquid crystal film 1 is preferably as follows Figure 2 After being bonded to another film 4 via the adhesive layer 3 as shown in C, Figure 2 The film substrate 8 is peeled off as shown in D. By bonding the film 4 with the adhesive layer 3 through the adhesive layer 3, a laminated optical film in which the oriented liquid crystal film is firmly bonded to the film 4 can be obtained.
[0112] The optical properties of the oriented liquid crystal film are not particularly limited. The vertically oriented liquid crystal film is a positive C plate with an in-plane retardation of approximately 0 (e.g., less than 5 nm, preferably less than 3 nm) and a negative thickness retardation (having a refractive index anisotropy of nz>nx=ny). The thickness retardation R represented by the product of (nx-nz) and the thickness of the vertically oriented liquid crystal film is t For example, it is about -50 to -500 nm.
[0113] [Optical film with adhesive]
[0114] When the oriented liquid crystal film 1 and the image display unit 50 are bonded to form an image display device, it is preferable to use an optical film with an adhesive in which an adhesive layer 2 is preliminarily laminated on the surface of the oriented liquid crystal film 1. The optical film with an adhesive may include an adhesive layer on either the substrate surface 11 or the air surface 12 of the oriented liquid crystal film 1.
[0115] <Adhesive Layer>
[0116] The adhesive constituting the adhesive layer 2 is not particularly limited, and an adhesive having an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine polymer, a rubber polymer, etc. as a base polymer can be appropriately selected and used. In particular, an adhesive having excellent transparency, moderate wettability, cohesion and adhesion, weather resistance or heat resistance, etc., such as an acrylic adhesive or a rubber adhesive, is preferred. The thickness of the adhesive layer is appropriately set according to the type of the adherend, etc., and is generally about 5 to 500 μm.
[0117] When the adhesive layer is provided on the air surface 12 of the oriented liquid crystal film 1, as long as the oriented liquid crystal film 1 is provided on the film substrate 8 (see Figure 2 When the adhesive layer is provided on the air surface 11 of the oriented liquid crystal film 1, the adhesive layer 2 can be laminated on the substrate surface 11 after the film substrate 8 is peeled off from the oriented liquid crystal film 1 to expose the substrate surface 11 of the oriented liquid crystal film 1.
[0118] The adhesive layer 2 is laminated on the oriented liquid crystal film 1, for example, by attaching an adhesive previously formed into a sheet to the surface of the oriented liquid crystal film 1. The adhesive layer 2 may be formed by applying an adhesive composition on the oriented liquid crystal film 1 and then drying the solvent, crosslinking, photocuring, etc. In order to improve the adhesion (anchoring force) between the oriented liquid crystal film 1 and the adhesive layer 2, the surface of the oriented liquid crystal film 1 may be subjected to a surface treatment such as a corona treatment or a plasma treatment, or an easy-adhesion layer may be formed before the adhesive layer 2 is laminated.
[0119] Since the oriented liquid crystal film 1 is thin, it is difficult to say that the oriented liquid crystal film 1 alone has sufficient handling properties. Therefore, when the adhesive layer 2 is laminated on the substrate surface 11 of the oriented liquid crystal film 1, it is preferred that the oriented liquid crystal film 1 is disposed on the film substrate 8 ( Figure 2 A), after the air side 12 of the oriented liquid crystal film 1 is attached to the film 4 ( Figure 2 B), the film substrate 8 is peeled off from the substrate surface 11 of the oriented liquid crystal film 1 ( Figure 2 C) By laminating the oriented liquid crystal film 1 and the other film 4, the thickness is increased compared to the case of the oriented liquid crystal film 1 alone, and the handling properties are improved.
[0120] <Diaphragm>
[0121] Preferably, a diaphragm 9 is temporarily bonded to the surface of the adhesive layer 2. The diaphragm 9 protects the surface of the adhesive layer 2 before the optical film with adhesive is attached to the image display unit 50. As the constituent material of the diaphragm, plastic films such as acrylic acid, polyolefin, cyclic polyolefin, polyester, etc. are preferably used. The thickness of the diaphragm is usually about 5 to 200 μm. It is preferred that a demolding treatment is applied to the surface of the diaphragm. As a release agent, silicone-based materials, fluorine-based materials, long-chain alkyl-based materials, fatty acid amide-based materials, etc. can be listed.
[0122] <Other films>
[0123] The film 4 bonded to the oriented liquid crystal film 1 is not particularly limited, and any optically isotropic or anisotropic film generally used as an optical film can be used without particular limitation. The film 4 may be a single-layer film or a laminate of a plurality of films.
[0124] Specific examples of the film 4 include a phase difference film, a polarizer, a polarizer protective film, etc. The film 4 may be a functional film such as a viewing angle expansion film, a viewing angle restriction (peek prevention) film, or a brightness enhancement film.
[0125] For example, in a liquid crystal display device, a phase difference plate as an optical compensation film is sometimes arranged between the image display unit (liquid crystal unit) and the polarizer for the purpose of appropriately changing the polarization state of light emitted from the liquid crystal unit to the visual confirmation side and improving the viewing angle characteristics. In an organic EL display device, in order to suppress the external light from being reflected in the metal electrode layer and visually confirmed like a mirror, a 1 / 4 wavelength plate is sometimes arranged between the unit and the polarizer. In addition, by arranging a 1 / 4 wavelength plate on the visual confirmation side of the polarizer, the emitted light becomes circularly polarized light, so that even with respect to the visual confirmation person wearing polarized sunglasses, the appropriate image display can be visually confirmed.
[0126] The film 4 may also be a film having a predetermined function integrated with the oriented liquid crystal film 1. For example, when the oriented liquid crystal film 1 is a vertically oriented film (positive C plate) and the film 4 is a polarizing plate (circular polarizing plate) having a quarter wavelength plate and a polarizer from the oriented liquid crystal film 1 side, a circular polarizing plate capable of shielding reflected light even from external light in an oblique direction can be formed by laminating the vertically oriented liquid crystal film and the quarter wavelength plate. Such a circular polarizing plate is used, for example, by being bonded to the surface of an organic EL unit.
[0127] <Adhesive>
[0128] The oriented liquid crystal film 1 and the film 4 are preferably bonded via a suitable adhesive layer 3. The material of the adhesive is not particularly limited as long as it is optically transparent, and examples thereof include epoxy resins, silicone resins, acrylic resins, polyurethanes, polyamides, polyethers, polyvinyl alcohol, and the like. The thickness of the adhesive layer 3 is, for example, about 0.01 to 20 μm, and is appropriately set according to the type of adherend or the material of the adhesive. When a curing adhesive that exhibits adhesion through a cross-linking reaction after coating is used, the thickness of the adhesive layer 3 is preferably 0.01 to 5 μm, and more preferably 0.03 to 3 μm.
[0129] As the adhesive, various adhesives are used, such as water-based adhesives, solvent-based adhesives, hot melt adhesives, active energy ray-curable adhesives, etc. Among them, water-based adhesives or active energy ray-curable adhesives are preferred because the thickness of the adhesive layer can be reduced.
[0130] As the water-based adhesive, for example, adhesives containing water-soluble or water-dispersible polymers such as vinyl polymers, gelatin, vinyl latex, polyurethane, isocyanate, polyester, and epoxy can be exemplified. The adhesive layer made of such a water-based adhesive is formed by applying an aqueous solution on the film and drying it. When preparing the aqueous solution, a cross-linking agent or other additives, a catalyst such as an acid, etc. may also be added as needed.
[0131] Examples of the crosslinking agent to be added to the water-based adhesive include boric acid or borax; carboxylic acid compounds; alkyl diamines; isocyanates; epoxies; monoaldehydes; dialdehydes; amino-formaldehyde resins; salts of divalent or trivalent metals and oxides thereof.
[0132] Active energy ray curing adhesives are adhesives that can undergo free radical polymerization, cationic polymerization, or anionic polymerization by irradiation with active energy rays such as electron beams or ultraviolet rays. Among them, photoradical polymerizable adhesives that initiate free radical polymerization by ultraviolet irradiation are preferred because they can be cured with low energy.
[0133] As monomers of the radical polymerizable adhesive, compounds having a (meth)acryloyl group or compounds having a vinyl group can be cited. Among them, compounds having a (meth)acryloyl group are suitable. As compounds having a (meth)acryloyl group, (meth)acrylic acid C 1-20Alkyl (meth)acrylates such as chain alkyl esters, alicyclic alkyl (meth)acrylates, and polycyclic alkyl (meth)acrylates; (meth)acrylates containing hydroxyl groups; (meth)acrylates containing epoxy groups such as glycidyl (meth)acrylates, etc. The radical polymerizable adhesive may also contain nitrogen-containing monomers such as hydroxyethyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, (meth)acrylamide, and (meth)acryloyl morpholine. The radical polymerizable adhesive may also contain polyfunctional monomers such as tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, cyclic trimethylolpropane formal acrylate, dioxanediol diacrylate, and EO-modified diglycerol tetraacrylate as crosslinking components.
[0134] Photocurable adhesives such as photoradical polymerizable adhesives preferably contain a photopolymerization initiator. The photopolymerization initiator can be appropriately selected according to the reaction species. For example, in the radical polymerizable adhesive, as a photopolymerization initiator, it is preferred to mix a photoradical generator that generates free radicals by light irradiation. Specific examples of the photoradical generator are described below. The content of the photoradical generator is generally about 0.1 to 10 parts by weight, preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of the monomer. It should be noted that when the radical polymerizable adhesive is used as an electron beam curing type, the photopolymerization initiator is not particularly necessary. In the radical polymerizable adhesive, a photosensitizer represented by a carbonyl compound or the like may also be added as needed. The photosensitizer is used to increase the curing speed or sensitivity using electron beams. The amount of the photosensitizer used is generally about 0.001 to 10 parts by weight, preferably 0.01 to 3 parts by weight, relative to 100 parts by weight of the monomer.
[0135] The adhesive may also contain suitable additives as required. Examples of additives include coupling agents such as silane coupling agents and titanium coupling agents, adhesion promoters such as ethylene oxide, ultraviolet absorbers, anti-deterioration agents, dyes, processing aids, ion traps, antioxidants, adhesion-imparting agents, fillers, plasticizers, leveling agents, foaming inhibitors, antistatic agents, heat stabilizers, hydrolysis-resistant stabilizers, etc.
[0136] <Photocuring of Adhesive>
[0137] As described above, the oriented liquid crystal film 1 can adjust the ratio of the horizontal load in the depth direction by adjusting the amount of light irradiation during the photocuring of the polymer of the photopolymerizable liquid crystal compound. If unreacted photopolymerization initiator remains in the oriented liquid crystal film, the polymerization (photocuring) of the photopolymerizable liquid crystal compound of the oriented liquid crystal film 1 may be performed by light irradiation during the curing of the adhesive.
[0138] When the adhesive layer 3 is photocured, if the oriented liquid crystal film is photocured, the hardness of the deeper portion than the surface layer (interface) becomes relatively high, and even immediately after the liquid crystal composition is photocured, the hardness of the liquid crystal film may be relatively high. 30 / F 15 In order to orient the F 30 / F 15 It is preferable to maintain the content within an appropriate range and suppress the photocuring of the aligned liquid crystal film during irradiation with light for curing the adhesive.
[0139] In order to suppress the curing of the oriented liquid crystal film during the photocuring of the adhesive, for example, it is sufficient to irradiate light having a longer wavelength than the irradiation light used for the photocuring of the liquid crystal composition during the photocuring of the adhesive. If relatively long-wavelength light is irradiated during the photocuring of the adhesive, it is difficult to photocure the oriented liquid crystal film which is sensitive to short-wavelength light, so it is possible to suppress the undesired photocuring of the oriented liquid crystal film.
[0140] The wavelength of light to be irradiated during photocuring depends mainly on the sensitivity wavelength of the photopolymerization initiator contained in the composition. Therefore, the photopolymerization initiator contained in the photocurable adhesive is preferably sensitive to a longer wavelength than the photopolymerization initiator contained in the liquid crystal composition. More specifically, the photopolymerization initiator contained in the photocurable adhesive is preferably an initiator that is sensitive to a wavelength longer than 380 nm, and more preferably an initiator that is sensitive to a wavelength longer than 400 nm. For the photocurable adhesive, it is preferred to use an initiator that has an extinction coefficient of 1×10 2 [mLg -1 cm -1 The photopolymerization initiator having long-wavelength light sensitivity may also have sensitivity to light having a wavelength of 400 nm or less.
[0141] Specific examples of the photopolymerization initiator having a photosensitivity of 400 nm or more in wavelength include acylphosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide ("Lucirin TPO" manufactured by BASF) and 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide ("Lucirin TPO-L" manufactured by BASF); aminoketones such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1 ("Irgacure 369" manufactured by BASF); and bisacylphosphine oxides such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide ("Irgacure 819" manufactured by BASF) and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide ("CGI403" manufactured by BASF).
[0142] As a photopolymerization initiator with a photosensitivity of a long wavelength, a light free radical generator that generates free radicals by extracting hydrogen can also be used. As a photopolymerization initiator that extracts hydrogen, thioxanthone-based photopolymerization initiators, benzophenone-based photopolymerization initiators, etc. can be listed. From the aspect that the free radical generation efficiency caused by light with a longer wavelength than 380nm is high and the absorption of visible light is small, thioxanthone-based photopolymerization initiators (light free radical generators) are preferred. As thioxanthone-based light free radical polymerization initiators, thioxanthone, dimethylthioxanthone, diethylthioxanthone, isopropylthioxanthone, chlorothioxanthone, etc. can be listed.
[0143] By using a photopolymerization initiator having long wavelength light sensitivity together with a photopolymerization initiator having low long wavelength light sensitivity, the photopolymerization initiator having long wavelength light sensitivity can be made to function as a sensitizer, so that the photopolymerization initiator having low long wavelength light sensitivity generates free radicals. In addition, a photoradical polymerization sensitizer such as thiopyrylium salt, merocyanine, quinoline, styrylquinoline, aryl ketones, aromatic ketones, ketocoumarin derivatives, anthracene derivatives, etc. can also be used together with the photopolymerization initiator.
[0144] As a light source of long-wavelength light for photocuring of the adhesive, a metal halide lamp encapsulated with gallium, an LED light source emitting light in the wavelength range of 380 to 440 nm, etc. are preferred. Alternatively, a light source containing ultraviolet light and visible light, such as a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a xenon lamp, etc., may be used, and a wavelength selection filter such as a bandpass filter or a long-pass filter may be used to shield short-wavelength ultraviolet light. The adhesive may also be photocured by irradiating light from a metal halide lamp encapsulated with gallium or an LED light source through a filter.
[0145] The cumulative irradiation light amount during the photocuring of the adhesive is, for example, 100 to 2000 mJ / cm 2 The above range can be set as long as the composition or thickness of the photocurable adhesive is appropriately adjusted. When the adhesive is photocured by irradiating light with a longer wavelength than that of the liquid crystal composition, the cumulative irradiation amount of UVV (ultraviolet-visible light with a wavelength of 395 to 445 nm) is preferably within the above range.
[0146] In order to suppress the photocuring of the oriented liquid crystal film during the photocuring of the adhesive, the photopolymerization initiator contained in the liquid crystal composition is preferably an initiator that has photosensitivity to short wavelengths compared to the photopolymerization initiator contained in the photocurable adhesive and does not show photosensitivity to long wavelength light. As a photopolymerization initiator that does not have photosensitivity to long wavelengths, it is preferred that the extinction coefficient at a wavelength of 405 nm is less than 1×10 2 [mLg -1 cm -1The photopolymerization initiator contained in the liquid crystal composition preferably has an extinction coefficient of less than 1×10 2 [mLg -1 cm -1 ] initiator. In addition, the photopolymerization initiator contained in the liquid crystal composition preferably has an extinction coefficient of 1×10 2 [mLg -1 cm -1 ] or above initiators.
[0147] Examples of photopolymerization initiators that do not have photosensitivity to long-wavelength light include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, and titanocene-based photopolymerization initiators.
[0148] Specific examples of photopolymerization initiators that do not show photosensitivity to long-wavelength light include benzophenone, 2,4,6-trimethylbenzophenone, 4-methylbenzophenone, hydroxycyclohexyl phenyl ketone ("Irgacure 184" manufactured by BASF), 2,2-dimethoxy-1,2-diphenylethane-1-one ("Irgacure 651" manufactured by BASF), 2-hydroxy-2-methyl-1-phenyl-propane-1-one ("Irgacure 184" manufactured by BASF), and 1,2-dimethoxy-2-diphenylethane-1-one ("Irgacure 184" manufactured by BASF). 1173”), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one (“Irgacure 2959” manufactured by BASF), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (“Irgacure 907” manufactured by BASF), 2-(dimethylamino)-1-(4-morpholinophenyl)-2-benzyl-1-butanone (“Irgacure 369” manufactured by BASF), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one (“Irgacure 127” manufactured by BASF), benzyl methyl ketal (“ESACURE 907” manufactured by DKSH) KB1”), 2-hydroxy-2-methyl-[4-(1-methylvinyl)phenyl]propanol oligomer (“ESACURE KIP150” manufactured by DKSH), and the like.
[0149] [Image display device]
[0150] An image display device can be formed by bonding the oriented liquid crystal film 1 to the surface of an image display unit 50 such as a liquid crystal unit or an organic EL unit via an adhesive layer 2. As described above, in forming the image display device, it is preferable to use an optical film with an adhesive in which an adhesive layer 2 is preliminarily provided on the surface of the oriented liquid crystal film 1. The optical film with an adhesive may also include an adhesive layer 2 for bonding to the image display unit on one surface of the oriented liquid crystal film 1, and another film 4 bonded to the other surface via an adhesive layer 3.
[0151] When poor lamination occurs after the optical film with adhesive is attached to the image display unit or a defect caused by a defect of the optical film is detected, the optical film is peeled off from the image display unit (rework). If there is a part with low strength (hardness) locally in the thickness direction of the film, sometimes the peeling force during rework causes cohesion failure in the part with low strength locally, which becomes the cause of poor rework. In the present invention, since the hardness distribution in the thickness direction of the oriented liquid crystal film is within the specified range, cohesion failure of the oriented liquid crystal film is not easy to occur, and the reworkability is excellent. Therefore, by using the oriented liquid crystal film of the present invention, the production efficiency of the image display device can be improved, and the yield rate of the product can also be expected to be improved.
[0152] Example
[0153] Hereinafter, the present invention will be described in more detail with reference to examples of production of a vertically aligned liquid crystal film, but the present invention is not limited to the following examples.
[0154] [Preparation of Liquid Crystalline Composition]
[0155] A liquid crystal composition is prepared by dissolving 20 parts by weight of a side chain liquid crystal polymer having a weight average molecular weight of 5000 of the following chemical formula (n=0.35, expressed as a block polymer for convenience), 80 parts by weight of a polymerizable liquid crystal compound showing a nematic liquid crystal phase ("Paliocolor LC242" manufactured by BASF), and 5 parts by weight of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one ("Irgacure907" manufactured by BASF) as a photopolymerization initiator in 400 parts by weight of cyclopentanone.
[0156]
[0157] [Production of oriented liquid crystal film]
[0158] As a film substrate, a biaxially stretched norbornene film having a slippery layer on one side (ZEONOR Film manufactured by Zeon Corporation of Japan, thickness: 33 μm, in-plane retardation: 135 nm, arithmetic mean roughness of the non-slippery layer-forming surface: 1.0 nm) was used. The above-mentioned liquid crystal composition was applied to the non-slippery layer-forming surface of the film substrate using a bar coater so that the thickness after drying would be 1 μm, and the liquid crystal was oriented by heating at 80° C. for 2 minutes. Thereafter, the orientation was fixed by cooling to room temperature, and the liquid crystal monomer was photocured by irradiating with ultraviolet rays (UVA: 320 to 390 nm) with the cumulative light amount shown in Table 1 in a nitrogen atmosphere, thereby producing an oriented liquid crystal film. During the irradiation of ultraviolet rays, the H valve of an electrodeless UV lamp system (“LIGHT HAMMER 10” manufactured by Heraeus) was used, and the cumulative light amount of UVA was measured by a UV illuminance measurement system (“UV Power Puck II” manufactured by Heraeus).
[0159] [Production of optical film with adhesive]
[0160] A photocurable adhesive composition was prepared by mixing 62 parts by weight of hydroxyethyl acrylamide ("HEAA" manufactured by Kojin), 25 parts by weight of acryloyl morpholine ("ACMO" manufactured by Kojin), 7 parts by weight of PEG400# diacrylate ("LIGHT ACRYLATE 9EG-A" manufactured by Kyoeisha Chemical), 3 parts by weight of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one ("Irgacure 907" manufactured by BASF) and 3 parts by weight of 2,4-diethylthioxanthone ("KAYACURE DETX-S" manufactured by Nippon Kayaku) as a photopolymerization initiator. The photocurable adhesive composition was applied to the surface of a stretched retardation film having a thickness of 48 μm at a thickness of 1 μm, and the above-mentioned oriented liquid crystal film was attached to the coating layer of the adhesive, and then irradiated with a cumulative light amount of 700 mJ / cm 2 The adhesive is cured by ultraviolet-visible light (UVV: 395-445 nm). For ultraviolet irradiation, a V-valve of an electrodeless UV lamp system ("LIGHT HAMMER 10" manufactured by Heraeus) is used, and short-wavelength light is cut off by a long-pass filter with a cutoff wavelength of 380 nm. The cumulative light amount of UVV is measured by a UV illuminance measurement system ("UV Power Puck II" manufactured by Heraeus).
[0161] The film substrate was peeled off from the oriented liquid crystal film, and an easily adhesive layer having a thickness of about 30 nm was formed on the surface of the oriented liquid crystal film. A 15 μm thick acrylic pressure-sensitive adhesive sheet was bonded thereon to obtain an optical film with pressure-sensitive adhesive.
[0162] [evaluate]
[0163] <Horizontal load>
[0164] The oriented liquid crystal film (film attached to the film substrate) before the stretched film is attached is fixed on the stage of the nanoindentation system (Hysitron's "TI950TriboIndenter"). A Berkovich (triangular pyramid) type diamond indenter (curvature radius of the front end: 0.1 μm) is used, and a load is applied to press to a depth of 15 nm. The stage is moved horizontally by 10 μm (movement speed is 0.5 μm / second), and the maximum value of the load within the range of the horizontal movement distance of 0.2 μm is set as the horizontal load F. 15 The indentation depth of the indenter was changed to 30 nm, and the horizontal load F was measured in the same manner. 30 .
[0165] <Anchoring force>
[0166] The optical film with adhesive was cut into a width of 50 mm and a length of 200 mm, and the surface of the stretched phase difference film side was attached to a glass plate with double-sided tape. The ITO film cut into a width of 25 mm and a length of 200 mm was attached to the acrylic adhesive sheet of the optical film with adhesive, and was left to stand at room temperature for 20 minutes as a measurement sample. The peeling force (peeling force at the interface of the oriented liquid crystal film and the acrylic adhesive layer) obtained by a 180° peeling test at a tensile speed of 300 mm / min using a tensile compression tester (Minebea "TCM-1kNB") was set as the anchoring force.
[0167] <Reworkability>
[0168] The polarizer with adhesive was cut into a rectangle of 150 mm × 150 mm, and the optical film with adhesive was attached to a Corning alkali-free glass plate using a hand roller. The film was peeled off from the glass plate in parallel along the long side from the short side to check whether there was any adhesive or the like remaining on the surface of the glass plate. For each sample, the rework test was performed 10 times, and the reworkability was determined according to the following criteria.
[0169] ○: All 10 samples had no residue on the glass surface and were reworked well.
[0170] △: Residues on the glass surface were seen in 1 to 3 samples (rework failure)
[0171] ×: Residues on the glass surface were observed in 4 or more samples (rework failure)
[0172] The integrated light intensity and evaluation results of the aligned liquid crystal films during photocuring of the experimental examples are shown in Table 1, and the integrated light intensity and the horizontal load of the aligned liquid crystal films are plotted in a graph shown in Figure 4In addition, the sample 3 (cumulative light intensity of 250mJ / cm 2 A cross-sectional image of an optical film with an adhesive prepared by aligning a liquid crystal film with an adhesive using a transmission electron microscope (TEM) is shown in FIG. Figure 5 middle.
[0173] Table 1
[0174]
[0175] The total amount of light is 50mJ / cm 2 For sample 1, the F of the oriented liquid crystal film 30 / F 15 On the other hand, the total light intensity is 450mJ / cm 2 For the above samples 5 to 8, the F of the oriented liquid crystal film 30 / F 15 Big, accompanied by F 30 / F 15 As the anchoring force increases, a tendency is seen to decrease, resulting in rework defects.
[0176] like Figure 4 As shown in FIG. 1 , as the accumulated light intensity during the photocuring of the oriented liquid crystal film increases, a horizontal load F at a depth of 30 nm is observed. 30 The horizontal load F at a depth of 15 nm 15 Although it increases slowly with the increase of the accumulated light amount, it is similar to F 30 Therefore, it can be seen that as the cumulative light amount increases, there is a F 30 / F 15 The tendency to grow larger.
[0177] like Figure 5 As shown in the TEM image, the oriented liquid crystal film has regions with different contrast at the interface on the adhesive layer side (substrate surface when the oriented liquid crystal film is made) and the interface on the adhesive layer side (air surface when the oriented liquid crystal film is made). The composition of the oriented liquid crystal film in the thickness direction was analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), and the results confirmed that the concentration of side chain liquid crystal polymers is high near the interface, and the concentration of liquid crystal monomer polymers is relatively low (data not shown).
[0178] From the above results, it is believed that since the polymer concentration is high near the interface of the oriented liquid crystal film (region with a depth of about 15 nm), F 15 In contrast, in the region far from the interface, the monomer concentration is high, so as the polymerization caused by light irradiation proceeds, F 30 Increase. It is believed that: in the case of sample 1, F30 / F 15 When the F is small (e.g., less than 1), the overall strength of the oriented liquid crystal film is insufficient due to insufficient photocuring, so that the oriented liquid crystal film is cohesively broken during rework, which causes rework failure. On the other hand, it is believed that if the photocuring is excessive, F 30 / F 15 As the hardness increases, the difference in hardness between the interface vicinity and the center portion in the thickness direction of the oriented liquid crystal film becomes significant, and cohesive failure is likely to occur near the interface where the hardness is relatively low, which may cause rework defects.
[0179] In contrast, F 30 / F 15 For samples 2 to 4 within the specified range, it is believed that: since the liquid crystal monomer is fully cured, the hardness of the oriented liquid crystal film is ensured. At the same time, since the hardness distribution in the thickness direction is small, it is not easy to cause cohesion failure due to local force concentration, showing good reworkability.
Claims
1. An oriented liquid crystal film, which is an oriented liquid crystal film made of a liquid crystal layer in which liquid crystal molecules are oriented in a predetermined direction, comprising two or more compounds, at least one of which is a polymer of a photopolymerizable liquid crystal compound, The horizontal load at a depth of 30 nm from the surface is 1 to 2.2 times the maximum horizontal load at a depth of 15 nm from the surface. When a triangular pyramid-shaped diamond indenter with a curvature radius of 0.1 μm at the front end is pressed into the sample to a depth of 15 nm or 30 nm using a nanoindenter, and the sample is moved 10 μm in a direction perpendicular to the depth direction, i.e., in a horizontal direction, at a moving speed of 0.5 μm / second, the maximum value of the load within the range of a moving distance of 0.2 μm is set as the horizontal load.
2. The oriented liquid crystal film according to claim 1, wherein: The two or more compounds include side chain liquid crystal polymers and polymers of photopolymerizable liquid crystal compounds.
3. The oriented liquid crystal film according to claim 2, wherein: The side chain type liquid crystal polymer has a monomer unit containing a liquid crystalline segment side chain and a monomer unit containing a non-liquid crystalline segment side chain.
4. The oriented liquid crystal film according to any one of claims 1 to 3, wherein The liquid crystal molecules are vertically aligned. 5 . An optical film with a pressure-sensitive adhesive, comprising: the oriented liquid crystal film according to claim 1 ; and a pressure-sensitive adhesive layer provided on a first main surface of the oriented liquid crystal film.
6. The optical film with adhesive according to claim 5, wherein The film further includes another film bonded to the second main surface of the aligned liquid crystal film via an adhesive layer.
7. An image display device, wherein: The oriented liquid crystal film according to any one of claims 1 to 4 is bonded to the surface of the image display unit via a pressure-sensitive adhesive layer.
8. A method for manufacturing an oriented liquid crystal film, which is a method for manufacturing an oriented liquid crystal film made of a liquid crystal layer in which liquid crystal molecules are oriented in a predetermined direction, comprising: A coating step of coating a liquid crystal composition containing a liquid crystal compound on a first main surface of a film substrate having a first main surface and a second main surface; A liquid crystal alignment step of heating the liquid crystal composition to align liquid crystal molecules in a predetermined direction; and A photopolymerization step of polymerizing or cross-linking the liquid crystal compound by light irradiation, The liquid crystal composition comprises two or more compounds, at least one of which is a photopolymerizable liquid crystal compound. The cumulative irradiation light amount in the photopolymerization step is 100 to 370 mJ / cm 2 , After the photopolymerization step, the maximum horizontal load of the aligned liquid crystal film at a depth of 30 nm from the surface is 1 to 2.2 times the maximum horizontal load at a depth of 15 nm from the surface. When a triangular pyramid-shaped diamond indenter with a curvature radius of 0.1 μm at the front end is pressed into the sample to a depth of 15 nm or 30 nm using a nanoindenter, and the sample is moved 10 μm in a direction perpendicular to the depth direction, i.e., in a horizontal direction, at a moving speed of 0.5 μm / second, the maximum value of the load within the range of a moving distance of 0.2 μm is set as the horizontal load.
9. The method for manufacturing an oriented liquid crystal film according to claim 8, wherein: The two or more compounds include a side chain type liquid crystal polymer and a photopolymerizable liquid crystal compound.
10. The method for manufacturing an oriented liquid crystal film according to claim 9, wherein: The side chain type liquid crystal polymer has a monomer unit containing a liquid crystalline segment side chain and a monomer unit containing a non-liquid crystalline segment side chain.
11. The method for producing an oriented liquid crystal film according to any one of claims 8 to 10, wherein: No alignment film is provided on the first main surface of the film substrate.
12. The method for producing an oriented liquid crystal film according to claim 11, wherein: The film substrate is a stretched film having an in-plane retardation of 10 to 500 nm.
13. A method for producing an optical film with an adhesive, comprising an oriented liquid crystal film made of a liquid crystal layer in which liquid crystal molecules are oriented in a predetermined direction, an adhesive layer provided on a first main surface of the oriented liquid crystal film, and another film attached to a second main surface of the oriented liquid crystal film via an adhesive layer, wherein: By the method according to any one of claims 8 to 12, an oriented liquid crystal film is provided on a film substrate to form a laminate in which a first main surface of the film substrate and a first main surface of the oriented liquid crystal film are in contact with each other, Another film is bonded to the second main surface of the oriented liquid crystal film via an adhesive layer. peeling the film substrate from the oriented liquid crystal film, An adhesive layer is laminated on the second main surface of the oriented liquid crystal film.
14. The method for producing an optical film with an adhesive according to claim 13, wherein: The adhesive layer is a light-curing adhesive. The light irradiated for photocuring the adhesive is light of a longer wavelength than the light irradiated for curing the photopolymerizable liquid crystal compound in the photopolymerization step when forming the aligned liquid crystal film.
Citation Information
Patent Citations
Liq. crystalline (LC) material
DE19504224A1
Novel polymerizable liquid crystalline compounds
DE4408171A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystalline copolymer
GB2280445A
Crosslinked organopolysiloxanes having liquid-crystalline properties
US4388453A
